Modeling synergy and individual effects of X-ray induced photodynamic therapy components - Farideh. S. Hossein; Nadia Naghavi; Ameneh Sazgarnia; Atefeh Vejdani Noghreiyan (Scientific Reports)
Abstract X-ray induced photodynamic therapy (XPDT) utilizes self-lighting nanoparticles to combine the benefits of radiotherapy and photodynamic therapy. These nanomaterials transform X-ray to visible light that can be absorbed by nearby photosensitizers and in the presence of surrounding oxygen molecules generates reactive oxygen species, which are very toxic to the cells. Despite many studies conducted on modelling XPDT, little focused on the contribution of each component as well as their synergy effects. We developed a multiscale physicochemical model of XPDT to incorporate the key role of molecular oxygen in PDT component efficiency. Simultaneously, the effects of RT in the presence of TiO2 nanoscintillators evaluated experimentally on HT-29 cell line. Simulation results predicted necrosis and apoptosis death of cancerous cells and estimated the minimum XPDT efficiency under specific conditions. The calculated synergism index estimated a synergism ratio greater than one indicated that tumor growth inhibition in XPDT is greater than the sum of each treatment component alone.